Expression of anti-Müllerian hormone in letrozole rat model of polycystic ovary syndrome. (December 2014) - Du, Dan-Feng; Li, Xue-Lian; Fang, Fang; Du, Mei-Rong
Abstract Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age with anti-müllerian hormone (AMH) two to three times higher, but the mechanism of increased AMH, excessive follicles and follicle stagnation in PCOS still needs further research. Methods: Female Sprague–Dawley rats were treated with a gavage of 1.0 mg/kg of letrozole carboxymethylcellulose solution once daily for 21 consecutive days. Serum steroid concentrations, ovarian morphology, ovarian expression of AMH and AMH-RII protein were determined and their relationships were studied. Results: According to the morphology and endocrinology, the letrozole model group was a successful PCOS model. Serum AMH and ovarian local expression of AMH and AMH-RII were both increased in letrozole model group. The elevated AMH had a positive correlation with T, growing follicle count and a negative correlation with body weight. Conclusions: The letrozole model group is a good animal model for the study of AMH in PCOS patients with obesity or insulin resistance. The increased serum AMH level in PCOS is the consequence of the androgen-induced excess of small antral follicles. These results lead to the hypothesis that reducing AMH may become a therapeutic target of PCOS, which is worth further research.